2006
DOI: 10.1152/ajpheart.00772.2004
|View full text |Cite
|
Sign up to set email alerts
|

Calpains: a physiological regulator of the endothelial barrier?

Abstract: The intracellular protease calpain, abundant in endothelial cells (EC), is assumed to be inactive under physiological conditions but may account for Ca2+ -linked pathophysiological events. However, nonstimulated EC contained autolyzed, activated calpain. Adding 12-48 microM calpain inhibitor I (CI) or 0.5-1 microM of the novel, membrane-permeable conjugate of calpastatin peptide-penetratin (CPP) caused rapid rounding and retraction of cultured EC (phase contrast, capacitance) and translocation of Syk, Rac, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Immunofluorescence-HUVECs were isolated and cultivated as described previously (23). Briefly, cells were cultured on 8-chamber -slides (Ibidi, Munich, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence-HUVECs were isolated and cultivated as described previously (23). Briefly, cells were cultured on 8-chamber -slides (Ibidi, Munich, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have reported that inhibition of calpain activity improves organ function in diabetic animal models (11,12) and in acute cardiovascular events (13). In vitro studies have now implicated calpains in the regulation of endothelial cell barrier (14,15).…”
mentioning
confidence: 99%
“…Mechanistically, calpainmediated regulation of small GTPases 13,40) as well as calpain-induced proteolysis of focal adhesion proteins 37) during EC dynamics has been documented previously. Accordingly, calpain systems appear to play key roles in angiogenesis 36,38) , wound closure 39) and maintenance of barrier functions 13,40) in ECs. In addition to motility responses, it has been reported that nitric oxide (NO) production in ECs is modulated through calpain-induced proteolysis of HSP90 42) or calpain-regulated PI3K/AMPK signaling 35) .…”
Section: Calpain and Vascular Integritymentioning
confidence: 73%
“…It is likely that VEGF 35,36) and fluid shear stress 13,37,38) are representative activators of calpain systems in ECs under physiological conditions. ECs exhibit measurable calpain activity even under unstimulated conditions 39,40) , which may be due to spontaneous Ca 2+ mobilization in the cells 41) . Mechanistically, calpainmediated regulation of small GTPases 13,40) as well as calpain-induced proteolysis of focal adhesion proteins 37) during EC dynamics has been documented previously.…”
Section: Calpain and Vascular Integritymentioning
confidence: 99%
See 1 more Smart Citation